Developments in industrial action 2003-2007 (Dublin, 2008)
"This overview examines developments in industrial action across the European Union and in Norway over the period 2003–2007. The data show that while overall levels of industrial action were low in historical terms during this period, there were considerable variations between countries. The most ‘strike-prone’ countries included Belgium, France and Spain, while Latvia and Lithuania were essentially strike-free. The level of action in the new Member States was only about a quarter of that in the former EU15; however, some new Member States have begun to see a rise in strike activity in recent times. Industry and manufacturing were the sectors most prone to conflict, followed by transport and communications, and the broad public sector. The most common cause of industrial action was disputes over pay."